Wanted: More Nails for the Hammer — An Investigation Into the Application of Human Computation - Brem, Elizabeth; Bick, Tyler; Schriner, Andrew; Oerther, Daniel (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
Researchers studying human computation and crowdsourcing know it as a useful tool for solving data analysis problems. Outside of this community, however, we ask the question ‘how many people with data analysis problems know how to use human computation and crowdsourcing?’ In this paper, we observe trends in academic papers on the topic of human computation and crowdsourcing, conduct a survey, and examine the growth of the human computation and crowdsourcing market by researching recent market reports in order to test the hypothesis that human computation and crowdsourcing is not a widely used tool despite its usefulness for problem solving.